2015
DOI: 10.1074/jbc.m115.684829
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-assisted Post-translational Transport of Plastidic Type I Signal Peptidase 1

Abstract: Background:In bacteria, type I signal peptidase is targeted to the membrane co-translationally. Results: Plastidic type I signal peptidase 1 (Plsp1) could insert into the membrane in an incorrect orientation, which was prevented by a stroma chaperone and the cpSec1 machine. Conclusion: Correct membrane insertion of Plsp1 is ensured by stromal components.Significance: The results demonstrate an adaptive mechanism of protein transport during organelle evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 73 publications
2
20
0
Order By: Relevance
“…It is likely that PsbO1 vigorously interacts with and needs protection from molecular chaperones before it is transported into thylakoid lumen; however, the interaction might be too weak and transient to be visualized by classical biochemical assays. The involvement of stroma chaperonin for thylakoid transport of plastidic type I signal peptidase has been recently reported [ 68 ]. By comparing two transgenic lines that bear the same PsbO1GFP allele, we showed that extra HSP90C facilitates the accumulation of PsbO1GFP mature form ( Fig 5B ) and more thylakoid association of GFP signal ( Fig 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that PsbO1 vigorously interacts with and needs protection from molecular chaperones before it is transported into thylakoid lumen; however, the interaction might be too weak and transient to be visualized by classical biochemical assays. The involvement of stroma chaperonin for thylakoid transport of plastidic type I signal peptidase has been recently reported [ 68 ]. By comparing two transgenic lines that bear the same PsbO1GFP allele, we showed that extra HSP90C facilitates the accumulation of PsbO1GFP mature form ( Fig 5B ) and more thylakoid association of GFP signal ( Fig 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…11,791,100;Invitrogen). The destination vector used for in vitro import and processing assays was pIVTGW-SP6, described in Endow et al (2015). The destination vector used for transient expression was pMDC32 (Curtis and Grossniklaus, 2003).…”
Section: Plasmidsmentioning
confidence: 99%
“…8N–Q ). As a control for non-specific effects in mutant protoplasts, we localized GFP fused to PLSP1, a thylakoid protein that is known to be targeted via an SRP-independent process ( Endow et al , 2015 ), in wild-type, srp43 , and srp54 protoplasts. PLSP1 has one TMD, a large C-terminus exposed to the thylakoid lumen, and a smaller N-terminus exposed to the stroma.…”
Section: Resultsmentioning
confidence: 99%